Monitoring of Short‐Term Erythropoietin Therapy in Rats with Acute Spinal Cord Injury Using Manganese‐Enhanced Magnetic Resonance Imaging. Issue 4 (16th December 2014) - Freitag, Martin Thomas; Márton, Gábor; Pajer, Krisztián; Hartmann, Jens; Walder, Nadja; Rossmann, Markus; Parzer, Peter; Redl, Heinz; Nógrádi, Antal; Stieltjes, Bram
ABSTRACT BACKGROUND AND PURPOSE To evaluate the short‐term outcome of erythropoietin (EPO) therapy in rats with spinal cord injury (SCI) using manganese‐enhanced magnetic resonance imaging (MEMRI). METHODS Rats were divided in an EPO and a control group. Laminectomy at Th11 was performed, followed by SCI. MnCl2 was applied into the cisterna magna and functional recovery was examined after injury using BBB‐scoring. Then, rats were euthanized and the spinal cord was extracted for MEMRI. Finally, histological analysis was performed and correlated with MEMRI. RESULTS EPO‐treated animals showed significantly better functional recovery (P = .008, r = .62) and higher mean signal‐to‐noise ratio (SNR) in MEMRI compared to controls for slices 10‐13 (P = .017, R2 = .31) at the level of the lesion epicenter. Functional recovery correlated significantly with higher SNR values, determined using the mean SNR between slices 10 and 13 (P = .047, R2 = .36). In this region, histology revealed a significantly decreased number of microglia cells and apoptosis in EPO‐treated animals. CONCLUSION MEMRI successfully depicts the therapeutic effect of EPO in early SCI that leads to a significant recovery in rats, a significantly reduced immune response and significantly reduced number of apoptotic cells at the height of the lesion epicenter.